Novel Munc13–4 mutations in children and young adult patients with haemophagocytic lymphohistiocytosis. Issue 12 (6th July 2006) - Santoro, A; Cannella, S; Bossi, G; Gallo, F; Trizzino, A; Pende, D; Dieli, F; Bruno, G; Stinchcombe, J C; Micalizzi, C; De Fusco, C; Danesino, C; et al.
Abstract : Familial haemophagocytic lymphohistiocytosis (FHL) is a genetically heterogeneous disorder characterised by constitutive defects in cellular cytotoxicity resulting in fever, hepatosplenomegaly and cytopenia, and the outcome is fatal unless treated by chemoimmunotherapy followed by haematopoietic stem-cell transplantation. Since 1999, mutations in the perforin gene giving rise to this disease have been identified; however, these account only for 40% of cases. Lack of a genetic marker hampers the diagnosis, suitability for transplantation, selection of familial donors, identification of carriers, genetic counselling and prenatal diagnosis. Mutations in the Munc13–4 gene have recently been described in patients with FHL. We sequenced the Munc13–4 gene in all patients with haemophagocytic lymphohistiocytosis not due to PRF1 mutations. In 15 of the 30 families studied, 12 novel and 4 known Munc13–4 mutations were found, spread throughout the gene. Among novel mutations, 2650C→T introduced a stop codon; 441del A, 532del C, 3082del C and 3226ins G caused a frameshift, and seven were mis sense mutations. Median age of diagnosis was 4 months, but six patients developed the disease after 5 years of age and one as a young adult of 18 years. Involvement of central nervous system was present in 9 of 15 patients, activity of natural killer cells was markedly reduced or absent in 13 of 13 tested patients. Chemo-immunotherapy was effective in all patients. Munc13–4 mutations were found in 15 of 30 patients with FHL without PRF1 mutations. Because these patients may develop the disease during adolescence or even later, haematologists should include FHL2 and FHL3 in the differential diagnosis of young adults with fever, cytopenia, splenomegaly and hypercytokinaemia.